An efficient preprocessing method to suppress power harmonic noise for urban towed transient electromagnetic measurement data. (December 2021) - Sun, Yishu; Huang, Sihe; Zhang, Yang; Lin, Jun
Abstract: Towed transient electromagnetic method (TEM) is an efficient geophysical method for urban underground space measurement. However, compared with the field environment, the power harmonic noise as urban electromagnetic noise is the key reason for the low signal-to-noise ratio (SNR) of the towed TEM data. We propose an efficient preprocessing method based on a multi-step processing strategy, which can fast suppress power harmonic noise and improve SNR. Firstly, a pure power harmonic noise sample is obtained by the least-square fitting. Secondly, the noise component of the measurement data that is most relevant to this sample is quickly searched by an improved genetic algorithm. Finally, the power harmonic noise component is subtracted from the measurement data, and the SNR is significantly improved. The simulation and field experiments show that the new method can fast and effectively suppress power harmonic noise without signal distortion, and it is especially suitable for towed data processing.